Creative thinking of characters and plot dynamics in the novel Bumi by Tere Liye - Miftakhul Huda; Irfai Fathurohman; Abdulkarim Duerawee (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Creative thinking is an important competency in facing the challenges of the 21st century, and literature is a medium for developing this ability. This article aims to uncover the representation of characters' creative thinking and the relationship between plot dynamics in the novel Bumi by Tere Liye. The study focuses on the main characters, namely Raib, Seli, and Ali, showing their creative thinking processes in dealing with conflicts and the dynamics of the storyline that support the development of creativity. The approach used is qualitative with content analysis techniques. Data were obtained from novel texts using intensive recording techniques of dialogues, narratives, and characters' actions that indicate the dimension of creative thinking. Analysis refers to creative thinking indicators that include fluency, flexibility, originality, and elaboration. The study's results show that the three main characters have different representations of creative thinking. Ali stands out more for fluency and flexibility. Raib shows originality in discovering his identity and distinctive strengths. Seli shows elaboration through creative actions that are directed and applicable in crises. The plot's progressive, surprising, and conflict-driven dynamics support the emergence of the characters' creative actions, forming an integration between characters and events. This study confirms that the novel Bumi not only presents fantasy stories but also serves as a relevant medium for developing creative thinking skills through creative literacy.